2021
DOI: 10.1021/acs.jafc.0c06949
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Reactivity Pattern of Tomato Seed and Peel Nonspecific Lipid-Transfer Proteins after in Vitro Gastrointestinal Digestion

Abstract: The influence of gastrointestinal digestion on the immunological properties of three different nonspecific lipid-transfer proteins (nsLTPs) described in tomato fruit has been assessed using an in vitro system mimicking the stomach and intestine digestion conditions. Tomato peel/pulp nsLTP, Sola l 3, was degraded after digestion, although the immunoglobulin E (IgE) recognition of intact protein and a 10 kDa band were still observed after 30 min of duodenal digestion in the presence of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, some studies have shown that conformational epitopes are more easily damaged than linear epitopes during digestion (Bøgh et al., 2013; Martín‐Pedraza et al., 2021; Wu et al., 2017). Conformational epitopes are susceptible to acidic and proteolytic environments during gastrointestinal digestion due to changes in protein conformation, whereas linear epitopes are only destroyed by proteolysis due to the location of a cleavage site (Bøgh & Larsen, 2021; Madsen et al., 2014).…”
Section: Structure–activity Relationships Of Food Allergens During Ga...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies have shown that conformational epitopes are more easily damaged than linear epitopes during digestion (Bøgh et al., 2013; Martín‐Pedraza et al., 2021; Wu et al., 2017). Conformational epitopes are susceptible to acidic and proteolytic environments during gastrointestinal digestion due to changes in protein conformation, whereas linear epitopes are only destroyed by proteolysis due to the location of a cleavage site (Bøgh & Larsen, 2021; Madsen et al., 2014).…”
Section: Structure–activity Relationships Of Food Allergens During Ga...mentioning
confidence: 99%
“…(2008) found that gastrointestinal digestion expanded the original protein folding structure of kiwi allergens, thus obtaining a great deal of hydrolyzed peptides with new epitopes (Lucas et al., 2008); these digested hydrolysates can combine with more IgE to enhance their allergenicity. Moreover, tomato peel/pulp nsLTP (Sola l 3) showed increased immunoreactivity after gastrointestinal digestion with an IgE‐binding value of 185% compared to the undigested protein, suggesting that the partial unfolding of Sola l 3 under acidic gastric conditions might unmask IgE epitopes (Martín‐Pedraza et al., 2021). Similar results have been described for α‐lactalbumin, where some linear epitopes retained on the antidigestive stable peptides were exposed after gastroduodenal digestion and played a more important role in triggering allergic reactions than conformational epitopes, resulting in increased allergenicity after digestion (X. Wang, Tu, Liu, et al., 2021).…”
Section: Structure–activity Relationships Of Food Allergens During Ga...mentioning
confidence: 99%
“…Nonspecific lipid transfer proteins (nsLTPs) are small, highly stable and conserved molecules involved in the plant defense against fungi and bacteria [ 2 , 3 ]. nsLTPs are found in high concentrations in the epidermal tissues of fruits and are the main allergens of fruits of the Rosaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…of allergy . Numerous methods, including skin prick test, immunoblotting, and enzyme-linked immunosorbent assay (ELISA, the most commonly used), have been adopted in terms of evaluating the allergenicity of food allergens. , Moreover, in vitro cell evaluation can mimic paths of allergenicity in vivo , which is convenient and, in particular, has provided an effective potential …”
Section: Introductionmentioning
confidence: 99%
“…12 Numerous methods, including skin prick test, immunoblotting, and enzyme-linked immunosorbent assay (ELISA, the most commonly used), have been adopted in terms of evaluating the allergenicity of food allergens. 13,14 Moreover, in vitro cell evaluation can mimic paths of allergenicity in vivo, which is convenient and, in particular, has provided an effective potential. 15 The reduction of the allergenicity of cow milk has been carried out by adopting numerous methods, including physical treatment and chemical processing, such as phosphorylation, glycation, and their combination.…”
Section: ■ Introductionmentioning
confidence: 99%